1999
DOI: 10.1038/sj.leu.2401448
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factors on acute promyelocytic leukemia and endothelial cells are differently regulated by retinoic acid, arsenic trioxide and chemotherapeutic agents

Abstract: The aberrant expression of tissue factor (TF) in acute promyelocytic leukemia (APL) cells has been implicated in the pathogenesis of the APL coagulopathy. In this study, we found that in APL patients receiving ATRA or As 2 O 3 treatment, the improvement in hypercoagulobility and hyperfibrinolysis paralleled the correction of plasma fibrinogen level and amelioration of bleeding symptoms. Notably, clinical improvement was also correlated to ATRA/As 2 O 3 -induced rapid decrease of membrane procoagulant activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 32 publications
4
37
0
3
Order By: Relevance
“…Since the mechanism of action of As 2 O 3 does not involve its binding to retinoic acid receptors (RARs), in contrast to that of retinoic acids (RAs), 4 we have examined the regulation of TM and TF expression in APL cell line, NB4 cells treated with As 2 O 3 alone or in combination with ATRA. Our data generally support a very recent report by Zhu et al, 5 which has appeared in this journal.…”
Section: Arsenic Trioxide (As 2 O 3 ) Gradually Downregulates Tissue supporting
confidence: 93%
See 2 more Smart Citations
“…Since the mechanism of action of As 2 O 3 does not involve its binding to retinoic acid receptors (RARs), in contrast to that of retinoic acids (RAs), 4 we have examined the regulation of TM and TF expression in APL cell line, NB4 cells treated with As 2 O 3 alone or in combination with ATRA. Our data generally support a very recent report by Zhu et al, 5 which has appeared in this journal.…”
Section: Arsenic Trioxide (As 2 O 3 ) Gradually Downregulates Tissue supporting
confidence: 93%
“…In cells treated with As 2 O 3 , the level of expression of TF mRNA decreased more gradually than that observed in cells treated with ATRA (Figure 3a), 3 tive of coagulopathy and hyperfibrinolysis fibrinogen/fibrin degradation products (FDP) and D-dimers gradually decreased and thus clinical improvement of DIC was also observed. 1,5 Whereas APL patients treated with ATRA show rapid improvement of coagulopathy within a few days, DIC in patients treated with As 2 O 3 improves in 1 week or more (personal communication by Dr Zhou Jin, First College of Harbin Medical University, Harbin, People's Republic of China). The effect of As 2 O 3 in inducing modest TF downregulation without TM upregulation, as shown in this study, seems to be compatible with the gradual and slow improvement of DIC in patients treated with As 2 O 3 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the low platelet level in APL results from repression of the normal hematopoiesis and increased consumption͞destruction level because of the coagulopathy. It is thus likely that combination therapy relieves the repression of hematopoiesis more significantly than mono-therapy (5,43). Third, the side effects of combination therapy could be well controlled.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 The As 2 O 3 was proved efficient in relapsed APL in many clinical studies, [4][5][6][7][8]13 being able to achieve a high CR rate and alleviate the abnormal coagulopathy. 14,15 In vitro study demonstrated that As 2 O 3 exerted dual effects on APL cells: with induction of apoptosis at higher concentration (1-2 mol/l) and partial differentiation at lower concentrations (0.1-0.5 mol/l). 9,16,22 The mechanism involved in inducing apoptosis has been clarified, 8,[17][18][19][20][21] but that of the differentiation effect is not well known.…”
Section: Discussionmentioning
confidence: 99%